Siting and building-massing considerations for the urban integration of active solar energy systems - Savvides, Andreas L.; Vassiliades, Constantinos; Michael, Aimilios; Kalogirou, Soteris A. (My University, 2019)
This paper aims to determine the optimum geometry of the building blocks in order to ensure the viable building integration of active solar energy systems in the urban fabric. Through literature review, similar research objectives are reported and analysed, whilst the building integration of active solar systems in urban areas is explored. The motivation for the proposed research emanates for a need for an analysis at the scale of urban blocks and of building massing configurations at the scale of a cluster of buildings rather than that of an individual building. These sets of physical characteristics are examined to arrive at simplified archetypes, while at the same time the habitation density is held constant. A set of twelve simplified building block configurations is created, whereby the geometrical parameters examined include the width of the streets separating the building blocks, the height of existing and proposed buildings and the massing configurations of the buildings that can be accommodated in the proposed building blocks. These parameters are manipulated to effect changes in collective building massing and siting decisions that result in the optimal integration of active solar energy systems that may be integrated on a building cluster's facades and roofs. Subsequently, the energy production potential of the buildings’ integrated systems was calculated for each case so that the twelve simplified massing and siting configurations could be compared and contrasted, so as provide architectural designers as well as planning authorities a way of quantifying solar planning decisions at the neighbourhood scale.
Keywords: Building insolation; Building integration; Building massing; Solar planning; Sustainable development; Urban design